NOVEL DRUG DELIVERY OF NANOPARTICLE-BASED CONTROLLED RELEASE SYSTEM AND THEIR EFFECTS ON TARGETTING CANCER CELLS-REVIEW - Iqra Haider; Zufi Shad; Hadia Naz; Uroosa Maqbool; Misbah Ali; Muntaha Iftikhar; Saba; Aleeza Rubab (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Nanoparticle-based drug delivery systems (NDDS) have gained significant attention for their potential to improve cancer therapy outcomes. These systems offer the ability to enhance drug delivery efficacy, improve therapeutic outcomes, and reduce adverse effects, making them a promising approach in cancer treatment. Objective: This systematic review aims to explore advancements in NDDS from 2007 to 2022, focusing on their role in revolutionizing cancer therapy by enhancing drug delivery efficacy, improving therapeutic outcomes, and minimizing side effects.Methodology: A comprehensive survey was conducted, analyzing sixty-five articles from reputable sources, including Google Scholar, Critical Reviews in Biotechnology, and various nanomedicine-focused publications. The review covers various types of nanoparticles, such as liposomes, polymer micelles, dendrimers, and inorganic nanoparticles, and their applications in cancer therapy.         Result: The review highlights the potential of different nanoparticles in improving cancer therapy. It discusses the use of magnetic and gold nanoparticles in hyperthermia, targeted drug delivery, and gene therapy. The study also emphasizes the importance of understanding nanoparticle properties and their interactions with biological systems to optimize therapeutic outcomes. Conclusion: While significant advancements in NDDS have been made, challenges remain in optimizing nanoparticle design, refining targeting strategies, and facilitating clinical translation. Continued research is essential to fully realize the potential of NDDS in cancer therapy.